Exogenous hydrogen sulfide enhances peach resistance to Monilinia fructicola through pathogenesis-related proteins, phenylpropanoid metabolism, and reactive oxygen species homeostasis - Gang Chen; Yi Chen; Yingying Wei; Shu Jiang; Jianfen Ye; Jiahui Chen; Feng Xu; Christian Chervin; Xingfeng Shao (Postharvest Biology and Technology, 2026)

Enhancing soy protein interfacial properties: Structural modification using stirred media milling for improved high internal phase emulsion stabilization - Yanyao Cui; David Julian McClements; Jun Chen; Xingfeng Xu; Xixiang Shuai; Changhong Li; Qin Geng; Jialong Han; Taotao Dai (Food Hydrocolloids, 2026)

Hydrogen sulfide reduces postharvest water loss in peach fruit by enhancing cuticular wax accumulation and inhibiting pectin degradation - Kaining Jin; Yi Chen; Manlin Wang; Yingying Wei; Shu Jiang; Jianfen Ye; Jiahui Chen; Feng Xu; Xingfeng Shao (Plant Science, 2026)

Role of 2-phenylethanol in regulating population density and biocontrol efficacy of Scheffersomyces spartinae W9 via quorum sensing - Siyi Wu; Xiurong Zou; Yingying Wei; Jiamei Li; Yi Chen; Shu Jiang; Jianfen Ye; Feng Xu; Xingfeng Shao (International Journal of Food Microbiology, 2026)

Preharvest spraying of alginate oligosaccharide improved the postharvest storability of peach fruit by inhibiting sucrose decomposition and cell wall degradation - Qianting Wu; Yingying Wei; Yi Chen; Shu Jiang; Jianfen Ye; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2026)

Onion aqueous extract enhances the nutritional quality of fresh-cut potatoes and its subsequent processing flavor - Jiayue Huang; Shu Jiang; Fengru Zhang; Yingying Wei; Yi Chen; Jianfen Ye; Feng Xu; Phebe Ding; Xingfeng Shao (Postharvest Biology and Technology, 2026)

Zinc regulates the balance of specific gut microbiota through MTF1/Nrf2 and mitigates ferroptosis through activation of PINK1/Parkin/mitophagy via the gut-kidney axis in sepsis-associated acute kidney injury in pregnant mice - Xingfeng Cheng; Yang Chen; Di Meng; Jie Ren; Xiaolong Yu; Huizhen Wang; Jun Guo (Apoptosis, 2026)

Contribution of various pectin fractions and internal condition to gel formation in wooly peach fruit during cold storage - Xiangwen Fang; Jianfen Ye; Cheng Li; Xi Yang; Jing Li; Yingying Wei; Shu Jiang; Yi Chen; Feng Xu; Xingfeng Shao (Food Chemistry, 2026)

Fucoidan enhanced brown rot resistance in postharvest peach fruit by regulating lignin biosynthesis - Yongyan Wu; Yi Chen; Yingying Wei; Feng Xu; Phebe Ding; Elsherbiny A. Elsherbiny; Fangming Wu; Xingfeng Shao (Food Bioscience, 2026)

Several small reservoir islands consistently support higher taxonomic, phylogenetic, functional, and interaction diversity than few large ones across multiple taxa - Yao Shen; Yuhao Zhao; Federico Riva; Wande Li; Chen Zhu; Xue Zhang; Ping Ding; Xingfeng Si (Biological Conservation, 2026)

Gelation of gellan in sucrose solutions as studied by rheology, particle tracking, micro-DSC, and 1H NMR measurements - Junhao Qiu; Weifeng Li; Haopeng Wang; Xingfeng Shao; Yi Chen; Yingying Wei; Jianfen Ye; Xi Yang (Food Hydrocolloids, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

PpMYC2 positively regulates chilling tolerance of peach fruit by suppressing sucrose degradation - Qian Li; Yingying Wei; Yi Chen; Shu Jiang; Jianfen Ye; Fangming Wu; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2026)

The formation mechanism of self-assembly composite gels - Dingyang Lv; Fusheng Chen; Lijun Yin; Xi Yang; Xingfeng Guo; Fengyan Lin (Journal of Food Engineering, 2026)

Curdlan modulates potato starch gelatinization and gelation: Mechanisms of interaction, structural enhancement, and texture improvement in hydrogel foods - Yongxin Liu; Xinyi Li; Liya Chen; Fan Feng; Chang Sun; Yingchao Xu; Xinyu Sun; Man Li; Qingjie Sun; Xingfeng Xu; Fengwei Xie; Yanfei Wang (Food Hydrocolloids, 2026)

A WRKY IIc transcription factor, FaWRKY47 enhances postharvest resistance to Botrytis cinerea in strawberry via activation of jasmonate biosynthesis and antioxidant defenses - Xin Ling; Yi Chen; Yingying Wei; Shu Jiang; Jianfen Ye; Jiahui Chen; Feng Xu; Fangming Wu; Xingfeng Shao (Postharvest Biology and Technology, 2026)

BoLrgB promotes programmed cell death of postharvest broccoli through regulating antioxidant pathways under oxidative stress - Jiacheng Li; Jiajun Lou; Jiahui Chen; Shifeng Cao; Yi Chen; Yingying Wei; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2026)

Interface characteristics and stability mechanism of high internal phase emulsions stabilised with modified peanut meal: Toward plant-based mayonnaise - Yan Liu; Tingwei Zhu; Xueying Liu; Xingfeng Guo; Lifen Zhang; Chenxian Yang; Yu Chen; Guanhao Bu; Fusheng Chen (Food Chemistry, 2026)

The PpERF4/PpERF061-PpCBF1 molecular cascade regulates sucrose metabolism to influence the cold resistance of peach fruit - Xingxing Wang; Yi Chen; Yingying Wei; Shu Jiang; Jianfen Ye; Jiahui Chen; Feng Xu; Elsherbiny A. Elsherbiny; Xingfeng Shao (Postharvest Biology and Technology, 2025)

PpWRKY4 regulates chilling injury in peach fruit by activating PpVIN2 and accelerating sucrose metabolism - Yongyan Wu; Shiyun Zhang; Yi Chen; Yingying Wei; Feng Xu; Phebe Ding; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Characterization and formation process analysis of peach fruit woolliness under low-temperature storage - Jiajia Xu; Jianfen Ye; Cheng Li; Yuqing Guo; Weixiang Jiang; Xi Yang; Yingying Wei; Shu Jiang; Yi Chen; Xingfeng Shao (Food Chemistry, 2025)

Quality changes in fragrant rapeseed oils derived from different varieties during roasting: Focusing on erucic acid and glucosinolate - Lingyan Zhang; Jia Chen; Xingfeng Guo; Yongsheng Cao; Guoyi Qu; Xiuzhu Yu (Food Chemistry, 2025)

Remediation of lead-zinc-cadmium co-contaminated soil using distiller's grain biochar immobilized with Lactobacillus plantarum - Guangxu Zhu; Xingfeng Wang; Rongkun Chen; Yunyan Wang; Xingyun Zhao; Panpan Wu; Qiang Tu (Chemical Engineering Journal, 2025)

The function of BoVDAC3 from broccoli in oxidative stress response and programmed cell death in BY-2 cells - Yuan Qian; Jiahui Chen; Shifeng Cao; Min Luo; Wenhui Jiao; Yi Chen; Yingying Wei; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2025)

Synergistic piezoelectric effect and oxygen vacancies in MoS2/BiOIO3 heterojunctions boosting photocatalytic degradation of 17β-estradiol - Chen Lin; Gongduan Fan; Jing Luo; Chenjian Cai; Xingfeng Cao; Kai-Qin Xu (Chemical Engineering Journal, 2025)

Declining floral color diversity alters bee color preferences in fragmented habitats - Hongjun Xie; Peng Ren; Chen Zhu; Juan Liu; Minghao Sun; Xingfeng Si; Ping Ding (Biological Conservation, 2025)

Spatiotemporal dynamics of migratory birds reshape seed dispersal and conservation implications on fragmented islands - Wande Li; Ingo Grass; Chen Zhu; Thomas Hiller; Marit Kinga Kasten; David Becker; Sara Tassoni; Ping Ding; Xingfeng Si (Biological Conservation, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

Jasmonic acid signaling pathway is involved in agaro-oligosaccharides-induced disease resistance of peach fruit through PpMYC2-activated transcription of PpPGIP1 - Qian Li; Yingying Wei; Shu Jiang; Jianfen Ye; Yi Chen; Feng Xu; Yongjiang Lou; Phebe Ding; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Preparation, interaction, and digestion of peanut oil body-based emulsion gels with xanthan gum and gallic acid - Tingwei Zhu; Shuoxing Wang; Di Yan; Lifen Zhang; Xingfeng Guo; Fusheng Chen (Food Hydrocolloids, 2025)

Broccoli stem extract enhances browning inhibition in fresh-cut peach fruit by inhibiting polyphenol oxidase activity and improving antioxidant capacity - Fengru Zhang; Shu Jiang; Shuang Jia; Boya Gui; Yingying Wei; Yi Chen; Jianfen Ye; Feng Xu; Phebe Ding; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Sucrose induces BoVDAC2 expression to preserve mitochondrial function and mitigate programmed cell death in broccoli - Min Luo; Jiahui Chen; Shifeng Cao; Xintong Guo; Yuan Qian; Wenhui Jiao; Hangjun Chen; Yi Chen; Yingying Wei; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2025)

Cinnamon essential oil causes cell membrane rupture and oxidative damage of Rhizopus stolonifer to control soft rot of peaches - Zichang Zhao; Mingxia Yu; Yingying Wei; Feng Xu; Shu Jiang; Yi Chen; Phebe Ding; Xingfeng Shao (Food Control, 2025)

Gene co-expression network analysis of the transcriptome identifies cold-resistant hub genes related to carbohydrate metabolism in peach fruit - Xianzhu Deng; Yingying Wei; Yi Chen; Phebe Ding; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Influence of triacylglycerol structure on the formation of lipid oxidation products in different vegetable oils during frying process - Jia Chen; Lingyan Zhang; Xingfeng Guo; Jie Qiang; Yongsheng Cao; Siyu Zhang; Xiuzhu Yu (Food Chemistry, 2025)

Natural or man-made disaster? Lessons from the extreme rain and flood disaster in Zhengzhou, China on "2021.7.20″ - Yan Zhu; Yun Liu; Ling Zhu; Min Liu; Zhiqiang Xie; Junxu Chen; Xingfeng Fu; Qisheng Wang; Zhanhui Wang; Qingyun Du (Sustainable Cities and Society, 2025)

Recent advances in the application of tea tree oil in the storage of fruit and vegetables - Xianzhu Deng; Yingying Wei; Shu Jiang; Jianfen Ye; Yi Chen; Feng Xu; Jiahui Chen; Xingfeng Shao (Postharvest Biology and Technology, 2025)

Agaro-oligosaccharides enhanced the Monilinia fructicola resistance of peach fruit by regulating antioxidative and phenylpropanoid metabolism - Qian Li; Yingying Wei; Yi Chen; Shu Jiang; Jianfen Ye; Feng Xu; Yongjiang Lou; Phebe Ding; Meriem Ouaziz; Xingfeng Shao (Postharvest Biology and Technology, 2024)

γ-aminobutyric acid (GABA) inhibits programmed cell death in fresh-cut pumpkin by maintaining mitochondria structural and functional integrity - Jiahui Chen; Jingyi Liang; Shifeng Cao; Hongfei Wang; Yingying Wei; Yi Chen; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2024)

Activation mechanism of fatty acids on membrane-bound polyphenol oxidase in peach fruit: Conformational change analysis and molecular docking simulation - Qiufang Zhu; Shu Jiang; Yingying Wei; Yi Chen; Jianfen Ye; Phebe Ding; Xingfeng Shao (Food Bioscience, 2024)

BomMDH1 regulates malate-mediated oxidative stress in tobacco BY-2 suspension cells - Haohui Chen; Shifeng Cao; Jiahui Chen; Hongfei Wang; Yingying Wei; Yi Chen; Xingfeng Shao; Feng Xu (Journal of Plant Physiology, 2024)

Adding carbon sources to the substrates enhances Cr and Ni removal and mitigates greenhouse gas emissions in constructed wetlands - Hongxu Chen; Bo Gao; Yuehong Guo; Qiankui Yu; Maosheng Hu; Xingfeng Zhang (Environmental Research, 2024)

Transcriptome analysis reveals the mechanism of antifungal peptide epinecidin-1 against Botrytis cinerea by mitochondrial dysfunction and oxidative stress - Li Fan; Yingying Wei; Yi Chen; Meriem Ouaziz; Shu Jiang; Feng Xu; Hongfei Wang; Xingfeng Shao (Pesticide Biochemistry and Physiology, 2024)

Transcriptome analysis reveals that trehalose alleviates chilling injury of peach fruit by regulating ROS signaling pathway and enhancing antioxidant capacity - Xingxing Wang; Yingying Wei; Shu Jiang; Jianfen Ye; Yi Chen; Feng Xu; Xingfeng Shao (Food Research International, 2024)

Influence of flavonoids from Sedum aizoon L. on mitochondrial function of Rhizopus nigricans in strawberry - Qingqing Ge; Shiyi Zhao; Xingfeng Shao; Yingying Wei; Jiahui Chen; Hongfei Wang; Feng Xu (World Journal of Microbiology and Biotechnology, 2024)

Hydrogen sulfide mediated methyl jasmonate -induced cold resistance in peach fruit - Miaomiao Yu; Yi Chen; Qiufang Zhu; Xuping Wu; Shu Jiang; Yingying Wei; Jianfen Ye; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2024)

Corrigendum to “PpZAT10 negatively regulates peach cold resistance predominantly mediated by inhibiting VIN activity” [Postharvest Biol. Technol. 190 (2022) 111952] - Yi Chen; Jiachang Sun; Yingying Wei; Kefeng Cao; Shu Jiang; Xingfeng Shao (Postharvest Biology and Technology, 2024)

Exogenous melatonin delays programmed cell death in broccoli via maintenance of ROS homeostasis and reduction of mitochondrial dysfunction - Zhiwei Jiang; Jiajun Lou; Shifeng Cao; Jiahui Chen; Hongfei Wang; Yingying Wei; Yi Chen; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2024)

Remote sensing retrieval of aerosol types in China using geostationary satellite - Xingfeng Chen; Haonan Ding; Jiaguo Li; Lili Wang; Lei Li; Meng Xi; Limin Zhao; Zhicheng Shi; Ziyan Liu (Atmospheric Research, 2024)

Transcriptomic analysis reveals the resistance mechanism of flavonoids from Sedum aizoon L. to Rhizopus nigricans in postharvest strawberry fruit - Qingqing Ge; Shiyi Zhao; Xingfeng Shao; Yingying Wei; Jiahui Chen; Hongfei Wang; Feng Xu (Postharvest Biology and Technology, 2024)

Combined application of alginate oligosaccharide and marine yeast Sporidiobolus pararoseus to control brown rot of peach fruit - Jiamei Li; Yingying Wei; Yi Chen; Jianfen Ye; Shu Jiang; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2024)

Generalist and topologically central avian frugivores promote plant invasion unequally across land‐bridge islands - Chen Zhu; Bo Dalsgaard; Wande Li; Fernando Gonçalves; Maximilian G. R. Vollstädt; Peng Ren; Xue Zhang; Junjie Shao; Ping Ding; Xingfeng Si (Ecology, 2024)
Seed dispersal by frugivorous birds facilitates plant invasions, but it is poorly known how invasive plants integrate into native communities in fragmented landscapes. We surveyed plant–frugivore interactions, including an invasive plant ( Phytolacca americana ), on 22 artificial land‐bridge islands (fragmented forests) in the Thousand Island Lake, China. Focusing on frugivory interactions that may lead to seed dispersal, we built ecological networks of studied islands both at the local island (community) and at landscape (metacommunity) levels. On islands with P. americana , we found that P. americana impacted local avian frugivory networks more on islands with species‐poor plant communities and on isolated islands. Moreover, as P. americana interacted mainly with local core birds (generalists), this indicates reduced seed dispersal of native plants on invaded islands. At the landscape level, P. americana had established strong interactions with generalist birds that largely maintain seed‐dispersal functions across islands, as revealed by their topologically central roles both in the regional plant–bird trophic network and in the spatial metanetwork. This indicates that generalist frugivorous birds may have facilitated the dispersal of P. americana across islands, making P. americana well integrated into the plant–frugivore mutualistic metacommunity. Taken together, our study demonstrates that the impact of plant invasion is context‐dependent and that generalist native frugivores with high dispersal potential may accelerate plant invasion in fragmented landscapes. These findings highlight the importance of taking the functional roles of animal mutualists and habitat fragmentation into account when managing plant invasions and their impact on native communities.

Evaluation of new nano-cutting fluids for the processing of carbon fiber-reinforced composite materials - Hongming Chen; Niancong Liu; Hu Lu; Xingfeng Li; Yuanyang Zheng (Journal of Cleaner Production, 2024)

A cyclodextrin metal-organic framework loaded with terpinen-4-ol and its application to control gray mold in strawberry - Lingling Yu; Xingxing Wang; Yingying Wei; Shu Jiang; Jianfen Ye; Yi Chen; Feng Xu; Hongfei Wang; Xingfeng Shao (Food Control, 2024)

1-Methylcyclopropene reduces postharvest water loss by modulating cuticle formation in tomato fruit - Xuping Wu; Yi Chen; Jingjing Zhu; Ni Zhang; Yingying Wei; Shu Jiang; Jianfen Ye; Xingfeng Shao (Postharvest Biology and Technology, 2023)

Widespread arboreal foraging behavior in ground-dwelling birds and the urgency of life-history studies - Wande Li; Chen Zhu; Ingo Grass; Peng Han; Yao Shen; Ping Ding; Xingfeng Si (Biological Conservation, 2023)

Prediction of daily PM2.5 and ozone based on high-density weather stations in China: Nonlinear effects of meteorology, human and ecosystem health risks - Lili Wang; Boya Liu; Rong Li; Xingfeng Chen; Lili Liu; Xiao Tang; Jingda Liu; Zhiheng Liao; Jinyuan Xin; Yuesi Wang; Bo Hu (Atmospheric Research, 2023)

Effects of microplastics on the phytoremediation of Cd, Pb, and Zn contaminated soils by Solanum photeinocarpum and Lantana camara - Qiankui Yu; Bo Gao; Ping Wu; Minni Chen; Chuanqian He; Xingfeng Zhang (Environmental Research, 2023)

Mannose delays senescence in broccoli florets via maintaining mitochondrial morphological structure and function - Xintong Guo; Shifeng Cao; Hongfei Wang; Yingying Wei; Yi Chen; Shu Jiang; Xingfeng Shao; Feng Xu (Postharvest Biology and Technology, 2023)

ERF transcription factor PpRAP2.12 activates PpVIN2 expression in peach fruit and reduces tolerance to cold stress - Kefeng Cao; Shiyun Zhang; Yi Chen; Jianfen Ye; Yingying Wei; Shu Jiang; Xingfeng Shao (Postharvest Biology and Technology, 2023)

Melatonin treatment delays postharvest senescence of broccoli with regulation of carotenoid metabolism - Jiajun Lou; Chenghao Wu; Hongfei Wang; Shifeng Cao; Yingying Wei; Yi Chen; Shu Jiang; Xingfeng Shao; Feng Xu (Food Chemistry, 2023)

Stability and release of peach polyphenols encapsulated by Pickering high internal phase emulsions in vitro and in vivo - Yu Song; Leyi Zhou; Decai Zhang; Yingying Wei; Shu Jiang; Yi Chen; Jianfen Ye; Xingfeng Shao (Food Hydrocolloids, 2023)

Epinecidin-1, a marine antifungal peptide, inhibits Botrytis cinerea and delays gray mold in postharvest peaches - Li Fan; Yingying Wei; Yi Chen; Shu Jiang; Feng Xu; Chundan Zhang; Hongfei Wang; Xingfeng Shao (Food Chemistry, 2023)

Deep Dermatophytosis Caused by Trichophyton rubrum - Junjun Sang; Kai Guo; Xingfeng Qi; Hongkun Wang; Shengping Chen (Mycopathologia, 2021)

Host plant environmental filtering drives foliar fungal community assembly in symptomatic leaves - Xiang Liu; Pu Jia; Marc W. Cadotte; Chen Zhu; Xingfeng Si; Yunquan Wang; Fei Chen; Jihua Wu; Shurong Zhou (Oecologia, 2021)

Interaction of Mn and Cd during their uptake in Celosia argentea differs between hydroponic and soil systems - Jie Liu; Guo Yu; Pingping Jiang; Xingfeng Zhang; Dejia Meng; Zhe Chen; Alan J. M. Baker; Rongliang Qiu (Plant and Soil, 2020)

Do seasonal species assemblages differ in their biogeography? Evidence from the spatial structure of bird communities on land‐bridge islands - Chuanwu Chen; Marcel Holyoak; Xingfeng Si; Yanping Wang; Ping Ding (Journal of Biogeography, 2018)
Aim We tested the effects of season and migratory status (residents‐versus‐seasonal migrants) on island biogeography of bird assemblages through partitioning beta diversity into richness and turnover components and community nestedness metrics. We predicted that total beta diversity, the richness component of beta diversity and community nestedness will be lower for bird assemblages in winter than in summer, and lowest of all for winter visitors. These predictions were derived from published ideas about resource availability, movement and habitat choice in birds in different seasons. Location Thousand Island Lake, China. Methods Bird species were sampled using line transects on 36 islands during five breeding and winter seasons (2009−2014). Birds were grouped into assemblages of winter residents, winter visitors and summer residents. Associations between beta diversity partitioning, island area, isolation and habitat richness were tested using partial Mantel correlations. We complemented these tests with measures of nestedness and null model approaches. Results Contrary to expectation, beta diversity, nestedness and difference of beta diversity or its components from null models were higher for winter residents than either summer resident or winter visitor assemblages. As predicted, winter visitors showed little association with habitat richness, and beta diversity was rarely different from null communities. Summer residents had the highest correlations of beta diversity components with habitat richness, but showed the lowest level of total beta diversity, a low richness component and were anti‐nested (less nested than random). Main conclusions Substantial differences were found in the biogeography of winter‐versus‐summer residents, and seasonal visitor (migratory)‐versus‐resident bird assemblages, which match expectations derived from bird biology and population ecology. Summer residents highlighted the role of habitat‐related niche differences, whereas winter residents showed area‐related selective extinction. By contrast, winter visitors appeared to be more randomly distributed.

Molecular cytogenetic identification of a novel dwarf wheat line with introgressed Thinopyrum ponticum chromatin - Guiling Chen; Qi Zheng; Yinguang Bao; Shubing Liu; Honggang Wang; Xingfeng Li (Journal of Biosciences, 2012)

Initial research on the polarized reflectance of typical urban surface types measured by the Directional Polarimetric Camera - DongHai Xie; XingFa Gu; TianHai Cheng; Tao Yu; ZhengQiang Li; XingFeng Chen; Hao Chen; Jing Guo (Science China Earth Sciences, 2011)